Peran Uang dalam Kesejahteraan Umat Buddha - Budianto Budianto; Sardi Sardi (STAB Maitreyawira, 2021)
Buddhists have varying economic status. Buddhists who are still economically weak are certainly less prosperous. The role of money is very important for mankind, because now everything needs money. By having an abundance of money, the welfare of Buddhists can be realized. With their wealth, Buddhists can contribute more economically to the welfare of the world. The purpose of writing this article is to find out the role of money in the welfare of Buddhists. The writing method is based on literature review from various sources of scriptures, books, articles and journals related to the role of money for the welfare of Buddhists. Buddhists, especially householders, are obliged to strive for the welfare of themselves and their families with Buddhist work ethics and earn a living according to Buddhist values. With the money they have, Buddhists can contribute more to the welfare of fellow human beings, especially for their families, nations and religions.